Persepsi Mahasiswa dalam Pembelajaran Berbasis E-Learning pada Program Studi Pendidikan Agama Islam - Jannah, Roudlotul; Masnawati, Eli (Lembaga Yasin AlSys, 2024)
This research was designed to find out how Islamic school students feel about e-learning. This research examines how students interpret e-learning, how they use it, and potential opportunities. Remarkable openings and challenges associated with e-learning in understanding learning. This research plan consists of a subjective descriptive examination. Students at Sunan Giri Surabaya College, namely the Islamic education program which is strictly focused on this program, is the subject of the exam. The research results show that there are both opportunities and challenges in implementing internet-based learning. Thus, the results of this research provide a comprehensive picture of how Islamic Religious Education students view e-learning. This can be used as a useful reference for building more innovative and flexible learning methods in the future.